Are heterobivalent GRPR- and VPAC1R-bispecific radiopeptides suitable for efficient in vivo tumor imaging of prostate carcinomas? - Lindner, Simon; Rudolf, Henning; Palumbo, Giovanna; Oos, Rosel; Antons, Melissa Joy; Hübner, Ralph; Bartenstein, Peter; Schirrmacher, Ralf; Wängler, Björn; Wängler, Carmen (Bioorganic & medicinal chemistry letters, 2021)
Receptor-specific peptides labeled with positron emitters play an important role in the clinical imaging of several malignancies by positron emission tomography (PET). Radiolabeled heterobivalent bispecific peptidic ligands (HBPLs) can target more than one receptor type and by this - besides exhibiting other advantages - increase tumor imaging sensitivity. In the present study, we show the initial in vivo evaluation of the most potent heterobivalent gastrin-releasing peptide receptor (GRPR)- and vasoactive intestinal peptide receptor subtype 1 (VPAC1R)-bispecific radiotracer and determined its tumor visualization potential via PET/CT imaging. For this purpose, the most potent described HBPL was synthesized together with its partly scrambled heterobivalent monospecific homologs and its monovalent counterparts. The agents were efficiently labeled with 68Ga3+ and evaluated in an initial PET/CT tumor imaging study in a human prostate carcinoma (PCa) xenograft rat tumor model established for this purpose. None of the three 68Ga-HBPLs enabled a clear tumor visualization and a considerably higher involvement in receptor-mediated uptake was found for the GRPR-binding part of the molecule than for the VPAC1R-binding one. Of the monovalent radiotracers, only [68Ga]Ga-NODA-GA-PESIN could efficiently delineate the tumor, confirming the results. Thus, this work sets the direction for future developments in the field of GRPR- and VPAC1R-bispecific radioligands, which should be based on other VPAC1R-specific peptides than PACAP-27.
Gesehen am 06.02.2023